Occupational pathogenesis of chlorine - Chirila, M.; Badulici, S.; Freilich, A.; Bica, N. (British Homeopathic Journal, 1994)
The occupational pathogenesis of chlorine in exposed workers are described and compared with the classic pathogenesis.4,5 The exposed group consisted of 82 men with occupational exposure to chlorine. The control group consisted of 46 men who were not exposed, all of them working in the same cellulose processing factory. The exposed group had the symptoms of the classical pathogenesis to a highly significant degree (p<0.001) compared to the unexposed control group.We found a number of symptoms, signs, disorders and syndromes which are not described in the classical pathogenesis, including: diminished tolerance to alcohol, back pain, pains in the joints dependent on weather conditions, dependent oedema, diminished taste sensitivity, persistent chronic hepatitis, hepatic steatofibrosis, chronic obstructive airways disease, polycythaemia with haemosiderosis and chronic conjunctivitis.The intensity of symptoms and signs was in direct proportion to the duration of exposure to chlorine.
Keywords: Chlorine; Chlorum; Muriaticum acidum; Occupational exposure; Pathogenesis